DEVELOPING SPEAKING PROFICIENCY IN INDONESIAN EFL CLASSROOMS: A QUALITATIVE STUDY ON CHALLENGES AND SOLUTIONS - Halim, Nurfitriyah; Kasim, Nur Aeni; Pratiwi, Dian Fera (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2025)
Speaking is a fundamental skill in English language learning, yet it remains one of the most difficult to master for EFL (English as a Foreign Language) learners. This study explores the key challenges that hinder speaking proficiency in Indonesian EFL classrooms and identifies practical solutions to address these issues. Using qualitative methods, classroom observation, teacher interviews, focus group discussions, and document analysis, the study reveals four major barriers: psychological factors such as anxiety and low confidence, instructional limitations including teacher-centered approaches and time constraints, limited exposure to authentic English input, and the absence of structured speaking assessments. The discussion connects these findings with recent pedagogical research from 2020 to 2025, emphasizing the need for affective support, communicative teaching methods, authentic language input, and formative speaking evaluation. This study contributes to a deeper understanding of speaking instruction in the Indonesian context and provides practical insights for educators and policymakers aiming to design effective, communicative EFL speaking programs. This study contributes not only to practical classroom strategies but also enriches the current understanding of affective and instructional barriers in EFL speaking development in Southeast Asia